MTOR pathway activation in large vessel vasculitis. (November 2018) - Maciejewski-Duval, A.; Comarmond, C.; Leroyer, A.; Zaidan, M.; Le Joncour, A.; Desbois, A.C.; Fouret, J.P.; Koskas, F.; Cluzel, P.; Garrido, M.; Cacoub, P.; Saadoun, D.
Abstract: Background: Mammalian target of rapamycin complex 1 (mTORC 1) drives the proinflammatory expansion of T helper (TH) type 1, TH17 cells and controls fibroblast proliferation, typical features of large vessel vasculitis (LVV) pathogenesis. Molecular pathways involved in arterial lesions of LVV are unknown. Methods: We evaluate mTORC pathway activation in vascular aorta lesions and in T cell homeostasis of patients with LVV. Results: Proliferation of both endothelial cells and vascular smooth-muscle cells was shown in vascular lesions in LVV. The vascular endothelium of proliferating aorta vessels from patients with LVV showed indications of activation of the mTORC1 pathway (S6RP phosphorylation). In cultured vascular endothelial cells, sera from patients with LVV stimulated mTORC1 through the phosphorylation of S6RP. mTORC1 activation was found also in Th1 and Th17 cells both systemically and in inflamed vessels. Patients with LVV exhibited a diminished S6RP phosphorylation in Tregs. Inhibition of mTORC1 pathway with rapamycin, increase Tregs and decrease effector CD4 + IFNγ +, CD4 + IL17 + and CD4 + IL21 + T cells in patients with LVV. Conclusions: We provided evidence that mTORC1 pathway has a central role in driving T cell inflammation and vascular lesions in LVV. Targeting mTORC pathway may represent a new therapeutic option in patients with LVV. Highlights: mTORC1 pathway is critical in driving vascular lesions and promoting effector T cells in large vessel vasculitis (LVV). Targeting mTORC pathway may represent a new therapeutic option in LVV. The inhibition of the mTORC pathway in LVV may prevent vascular remodeling and stenosis. Abstract : mTORC1 pathway has a critical role in driving vascular lesions and promoting effector T cells and suppressing Tregs in large vessel vasculitis (LVV). Targeting mTORC pathway may represent a new therapeutic option in patients with LVV.